Pillars of transformative leadership in the regulation of teacher assignment as school principal: A case from Indonesia - Farid Setiawan; Mufti Khakim (Universitas Ahmad Dahlan, 2026)
The Government of Indonesia has replaced its Ministry of Education Regulation Number 40 of 2021 with the Regulation Number 7 of 2025, which is well known as the Permendikdasmen No. 7/2025. This fundamental policy reform concerning the assignment of teachers as school principals was introduced to address structural challenges and evolving demands within the national education system. The regulatory shift reflects an effort to strengthen leadership quality in response to increasingly complex local, national, and global educational contexts. Accordingly, this article aims to explore the pillars of transformational leadership embedded in the new regulation and to examine their relevance to the projected profile of future school principals in Indonesia. This study uses a literature review with a descriptive-analytical approach that integrates analyses of regulatory materials, leadership literature, and relevant policy documents. The results of this study indicate that replacing regulations governing the assignment of teachers as school principals has led to fundamental shifts from administrative to visionary, ethical, inclusive, and adaptive leadership. Permendikdasmen No. 7/2025, as a new regulation, emphasizes the importance of moral integrity, shared motivation, innovation, and personal attention in creating transformative school principals. This regulation aligns with the needs of future school principals, as it clearly emphasizes school leaders with strong character, the ability to adapt to change, and a commitment to educational transformation. Overall, this new regulation offers a progressive paradigm that could improve the quality of school leadership in Indonesia. However, the limitation of this study lies in its focus on the analysis and interpretation of the material, without including empirical data on its implementation. Therefore, further research is needed to comprehensively explore actual practices and their impact on school performance.